Գրական տեքստը որպես սովորողների հանրամշակութային կոմպետենցիայի ձևավորման միջոց - Ավետիսյան, Էլեն
The literary text is an effective means of systematic teaching language and culture. A literary text, as the most effective means of developing intercultural competence, motivates, involves the reader in a kind of cognitive process, causes aesthetic pleasure, develops aesthetic taste, critical and creative thinking. Reading a literary text enables students to master the behavior patterns characteristic of a given ethno-cultural society, socio-cultural markers, socio-cultural norms, traditions and rituals. Literary text as an important means of forming public cultural competence performs functions of motivating, involving the reader in a unique cognitive process, giving aesthetic pleasure, developing aesthetic taste, critical and creative thinking. The reading of the literary-artistic text provides an opportunity to learn the models of behavior, cultural signs, cultural norms of communicative behavior, public and individual conventions, traditions and rituals characteristic of the given ethno-cultural community. Художественный текст является эффективным средством систематического обучения языку и культуре. Художественный текст, как наиболее эффективное средство развития межкультурной компетенции, мотивирует, вовлекает читателя в своеобразный познавательный процесс, вызывает эстетическое наслаждение, развивает эстетический вкус, критическое и творческое мышление. Чтение художественно-художественного текста дает возможность учащимся овладеть моделями поведения, характерными для данного этнокультурного общества, социо-культурными маркерами, социо-культурными нормами, традициями и ритуалами. Художественный текст как важное средство формирования общественной культурологической компетенции выполняет функции мотивации, вовлекая читателя в своеобразный познавательный процесс, доставляя эстетическое удовольствие, развивая эстетический вкус, критическое и творческое мышление.
Keywords: Մանկավարժություն